Compromised Dynamic Cerebral Autoregulation in Patients With Depression - Luo, Ming-Ya; Guo, Zhen-Ni; Qu, Yang; Zhang, Peng; Wang, Zan; Jin, Hang; Ma, Hong-Yin; Lv, Shan; Sun, Xin; Yang, Yi (Frontiers in Psychiatry, 2019)
Background: Patients with depression tend to have various comorbid neurological symptoms, but the mechanisms remain unclear. The purpose of this study was to analyze the characteristics of dynamic cerebral autoregulation in depressed patients. Methods: Patients (aged ≥ 18 years) who were diagnosed with depression (17-item Hamilton Depression Rating Scale [HAMD] > 17) or suspected of depression (HAMD > 7) were enrolled in this study. Medically healthy volunteers were recruited as controls. The subjects also received the 7-item HAMD. We simultaneously recorded noninvasive continuous arterial blood pressure and bilateral middle cerebral artery blood flow velocity from each subject. Cerebral autoregulation was assessed by analyzing the phase difference using transfer function analysis. Results: This study enrolled 54 patients with suspected depression, 45 patients with depression, and 48 healthy volunteers. The phase difference values were significantly lower in the patients with depression (mean F = 9.071, P < 0.001). In the multiple regression analysis, depression was negatively correlated with the phase difference values. Conclusions: Dynamic cerebral autoregulation was compromised in patients with depression and negatively correlated with the depression score. Improving dynamic cerebral autoregulation may be a potential therapeutic method for treating the neurological symptoms of depression.